P2X7 receptor activation awakes a dormant stem cell niche in the adult spinal cord - Falco, María Victoria; Fabbiani, Gabriela; Maciel, Cecilia; Valdivia, Spring; Vitureira, Nathalia; Russo, Raúl E. (Frontiers in Cellular Neuroscience, 2023)
The ependyma of the spinal cord is a latent stem cell niche that is reactivated by injury, generating new cells that migrate to the lesion site to limit the damage. The mechanisms by which ependymal cells are reactivated after injury remain poorly understood. ATP has been proposed to act as a diffusible "danger signal" to alert about damage and start repair. Indeed, spinal cord injury (SCI) generates an increase in extracellular ATP around the lesion epicenter that lasts for several hours and affects the functional outcome after the damage. The P2X7 receptor (P2X7r) has functional properties (e.g., low sensitivity for ATP, high permeability for Ca 2+ ) that makes it a suitable candidate to act as a detector of tissue damage. Because ependymal cells express functional P2X7r that generate an inward current and regenerative Ca 2+ waves, we hypothesize that the P2X7r has a main role in the mechanisms by which progenitor-like cells in the ependyma react to tissue damage. To test this possibility, we simulated the P2X7r activation that occurs after SCI by in vivo intraspinal injection of the selective agonist BzATP nearby the central canal. We found that BzATP rescued ependymal cells from quiescence by triggering a proliferative response similar to that generated by injury. In addition, P2X7r activation by BzATP induced a shift of ependymal cells to a glial fibrillary acidic protein (GFAP) phenotype similar to that induced by injury. However, P2X7r activation did not trigger the migration of ependyma-derived cells as occurs after tissue damage. Injection of BzATP induced the expression of connexin 26 (Cx26) in ependymal cells, an event needed for the proliferative reaction after injury. BzATP did not induce these changes in ependymal cells of P2X7 -/-mice supporting a specific action on P2X7r. In vivo blockade of P2X7r with the potent antagonist AZ10606120 reduced significantly the injury-induced proliferation of ependymal cells. Our data indicate that P2X7r has a key role in the "awakening" of the ependymal stem cell niche after injury and suggest purinergic signaling is an interesting target to improve the contribution of endogenous progenitors to repair.